Considérations sur le prêt commercial et la convention de prêt - Côté, Pierre-Paul (Les Cahiers de droit, 1987)
Commercial credit has been given many different forms over the years and the various financial instruments are being constantly refined. By the same token, loan agreements have become increasingly complex documents. The main thrust of this paper is to examine the legal nature, legality and usefulness of a number of financial instruments and clauses usually found in a typical agreement, in the light of basic civil law rules and principles. The first part of this paper deals with a number of financial instruments, namely the open credit agreement, the banker's acceptance, the letter of credit and the letter of guaranty. Secondly the author analyses the typical loan agreement focusing on the convenant 'sfundamentals elements and discussing its relationship with the use of sureties. In particular, two civil law mechanisms that are of some interest in connection with the loan agreement namely novation and subrogation are examined. The third and fourth parts of this paper deal with a number of standard clauses in the open credit and loan agreements.